Performance of mango varieties for growth, flowering and yield under agro climatic condition of Chhattisgarh plains (Indian Journal of Arid Horticulture, 2025)
Mango is one of the important fruit crops of Chattisgarh and is grown in an area of 8880 ha (excluding forest trees) with production of 79920 tonnes (Patil, 2002). The crop takes about three to four months from the time of fruit set to maturity and ripening. In northern India, mango is harvested during end of May to July-August, while in Chhattisgarh, mango fruits mature one month earlier than north India which offers immense scope for the local as well as for export market. Therefore, the study was conducted to find out appropriate varieties/hybrids suitable for the region to obtain maximum benefit from the mango.
Keywords: design; varieties/hybrids; Chattisgarh